Development of Father- and Mother-Child Intimacy and Their Association with Internalizing and Externalizing Problems among Early and Middle Chinese Adolescents. - Liu, Xin; Zhang, Yaoyao; Zeng, Jinyi; Jiang, Zhengyu; Liu, Yanling (Journal of Youth & Adolescence, 2025)
Parenting styles and the developmental environment of adolescents in China have undergone significant changes. However, the development of parent-adolescent intimacy among contemporary Chinese adolescents and its impact on internalizing and externalizing problems remain unclear. To address this research gap, this study explored the development of father-child and mother-child intimacy during early and middle adolescence and examined their effects on internalizing and externalizing problems. Further, it investigates the potential gender differences in these developmental processes. In total, 1,370 early adolescents (M age T1 = 12.31, SD age = 0.49; 51.17% girls) and 1381 middle adolescents (M age = 15.19, SD age = 0.50; 50.16% girls) participated in this one-year, three-wave longitudinal survey. The results showed that father-child and mother-child intimacy decreased over one year in early adolescents, while in middle adolescents, father-child intimacy increased, and mother-child intimacy decreased. Furthermore, the development of parent-child intimacy in both early and middle adolescents negatively predicted internalizing and externalizing problems one year later. Regarding sex differences, early adolescent girls had lower initial levels of father-child intimacy but higher initial levels of mother-child intimacy compared to boys. In middle adolescents, girls also showed higher initial levels of mother-child intimacy than boys. Additionally, the decline in father-child intimacy had a stronger impact on anxiety and aggression in early adolescent girls and a more significant effect on depression in middle adolescent girls. These findings offer new insights into how parent-child intimacy changes in Chinese adolescents and its impact on internalizing and externalizing problems, providing valuable guidance for targeted interventions.